ANTIBACTERIAL ACTIVITIES OF SOFT CORAL EXTRACTS Sinularia sp. ON PATHOGENIC BACTERIA (Escherichia coli, Staphylococcus aureus, AND Pseudomonas aeruginosa) - Sinuraya, Tri Setia Darma; Yoswaty, Dessy; Nursyirwani, Nursyirwani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTSoft coral extract of Sinularia sp. can inhibit pathogenic bacteria Escherichia coli, Staphylococcus aureus, and Pseduomonas aeruginosa with strong inhibitory power up to very strong inhibitory power. The purpose of this study was to determine the inhibition of Sinularia sp. extract against E. coli, S. aureus, and P. aeruginosa bacteria. This research was conducted in March - April 2019. Sampling was carried out in the waters of Tamiang Island, West Pasaman Regency, West Sumatra. The method of this research is the experimental method and the method used to test antibacterial activity is the agar diffusion method.Soft coral extract of Sinularia sp. very potential to inhibit pathogenic bacteria. The highest clear zone in E. coli bacteria with a concentration of 100% is 25.67 mm, the highest yield of S. aureus bacteria at a concentration of 100% with a yield of 22,05 mm,and the highest yield of P. aeruginosa bacteria at a concentration of 25% with a result of 24.62 mm. Clear zone increases in proportion to the increase in concentration, but in P. aeruginosa bacteria is inversely proportional, because the highest yield is obtained at a concentration of 25%. Keywords:Antibacterial Activity, Pathogenic Bacteria, Sinularia sp. Extract